(untitled) (Journal of the College of Education for Women, 2019)
The book of Alphendidad is considered as an important part of the holy book ofAvesta in the Zoroastrian religion. It is a religious and urbanization book that consists of anumber of chapters dealing with the creation. The book includes 22 chapters, mostly editedas a dialogue between Ahuaramzda the god of goodness and his prophet Zoroaster. Thebiggest chapter deals with the rules of purification of vices of the devil and dismissing it ofthe places around, hence it is the book of law of Zoroastrian about the important animals,birds , insects, and reptiles and their categorization according to their creation; creatures ofthe spirit of goodness and creatures of the spirit of evilness.Some of these creatures are included for their influence upon the life, nature, andother creatures, in addition to their influence upon the religious life. This is the focus of thecurrent study that sheds light on the identity of these creatures and their effect on thementality and the Zoroastrian belief.1. The Alphendidad is considered as the important idiosyncratic legislative part in thebook of Avesta, in which there is a lot of the legislations and laws that rule theindividual and social life and the consequences of the deeds of man as a rewardand punishment.2. The study tries to concentrate on a specific part of the book of Alphendidad andstudy it. It surveys the most important creatures in the book, especially animals,birds, insects, and reptiles – according the Zoroastrian belief -. The Zoroasterdivides theses creatures into two types according to the creation and impotence.The blessed creatures of goodness that created by the god of goodness,Ahoramzda; and cursed creatures of evilness created by the god of evilness,Ahrimn. 3. The ideas, points of views, rituals, and worships included in the book ofAlphendidad disagree with the common sense and any logical thinking. This is adefect against the Zoroastrian belief and thinking. The legend and myth is the onlymeans by which events are explained especially the creation and the view of theworld that is ruled by these two forces; the force of goodness and its creatures andthe force of evilness and its creatures.4. The human mind tends more to believe in myth and legend to explain mysteriousphenomena. Along history, Persians tend to weave legendry events in literatureresulting from their worshiping of natural phenomena that are difficult to beexplained in another way. They have found that the clear blue sky, light, fire, air,and water are divine and good creatures. They have even called the sun and the eyeof god and light as the son of god. And darkness, drought, and sickness are divine,cursed, and evil creatures.5. The creation is focused on the good creatures especially livestock, small and biganimals, dogs, and birds as the creatures of goodness. the study concentrates alsoon how to work on protectin and mentaining these creatures as the means ofvictory for the god of light, Ahoramzada against the cursed creatures of evilness.Therefore, Zoroaster imposes on his followers that they should sanctify thesecreatures and never harm them or killing them with no right.6. The Ancient Persian thinking has missed the fact that this world and its creaturesare the creation of one sole God. The question that raises here is weather theZoroastrian religion is a multiple-god or standard religion. Researches disagree toanswer this question. Some of them see the world with its two forces of goodnessand evilness are but two conflicting forces of the same God, and others believe thatZoroaster is standard theologically and philosophically he is a multiple-godreligion.7. The categorization of the animals, birds, insects, and reptiles into two typesaccording to the Zoroastrian belief is an evidence of ignorance and lack ofawareness. All creatures are the creation of the One sole God. The Zoroastrian hasdivided these creatures into two types according to their features, work and theireffect on nature among other useful or harmful creatures. The religion imposes the mythical and legendary view picturing these creatures as animals, birds, insectsaccording to their importance.8. The Zoroastrian religion exaggerates the importance of these creatures. It sanctifyand blessed the useful creatures and its remnants, as it considered the cow as avery important creature by Ahoramzda. Its importance lies in the fact that the cowis the source of their food, a means of cultivating their lands. Cow is considered asthe capital of the farming communities, and since the Parisian is an old agrariansociety, the cow and ox are important supplements. Yet there is a great deal ofexaggeration in dealing with the cow to an illogical extent of considering its urineas a sacred thing for purification of sins instead of holy water, which a thing thatgoes against proper and common test.9. The study signifies a group of animals described by Zoroaster as creatures ofgoodness as they have good and useful features according to the god of goodness,Ahoramzda. These animals are: Cow, Awl, fox, ox, camel, donkey, sheep, horse,bird, dog, goat, and eagle).10. The study also identifies a group of creatures that are considered as harmful –according to Zoroastrain religion – that affects the good creatures and affects thenature and spoil it. Zoroaster has allowed the destruction and killing thesecreatures and its harm to support the force of goodness over evilness. It alsoconsidered the destruction of these creature as part of the important religiousrituals of the Zoroastrian belief to purgation of sins and evils and to get nearer tothe god of goodness Ahoramzda. These creatures are: rats, locusts, snakes, flies,wolves, turtles, frogs, spiders, scorpions, lice, ants).